Growth and structural changes in transition countries: the chicken or the egg? - Olczyk, Magdalena; Kordalska, Aleksandra (Journal of Business Economics and Management, 2018)
The objective of this study is to test empirically the relationship between structural changes (changes in gross value added and employment) and economic growth. We used a panel Granger-causality analysis based on annual data for eight transition countries, covering the period 1995–2011. The main finding is that the causality relations analysed are heterogeneous processes and are identified more often when we measure structural changes by value added than by changes in employment. Among the countries analysed, we separate a subgroup of economies with very strong bilateral causality (small countries such as Latvia, Lithuania, and Estonia), a subgroup in which no causal relationships are observed (e.g., Hungary in the case of employment), and a group with a one-directional relationship (e.g., Poland, where GDP changes cause employment changes, but not vice versa). The research results point to the necessity of taking into account different relationships, whether one- or two-directional, between growth and structural changes in government economic policy. The paper presents a verifiable methodology, which was originally used to identify the analysed relationship in transition countries.